2016
DOI: 10.1002/lom3.10144
|View full text |Cite
|
Sign up to set email alerts
|

Correction of profiles of in‐situ chlorophyll fluorometry for the contribution of fluorescence originating from non‐algal matter

Abstract: In situ chlorophyll fluorometers have been widely employed for more than half a century, and to date, it still remains the most used instrument to estimate chlorophyll‐a concentration in the field, especially for measurements onboard autonomous observation platforms, e.g., Bio‐Argo floats and gliders. However, in deep waters (> 300 m) of some specific regions, e.g., subtropical gyres and the Black Sea, the chlorophyll fluorescence profiles frequently reveal “deep sea red fluorescence” features. In line with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 48 publications
(87 reference statements)
2
68
0
Order By: Relevance
“…As Proctor and Roesler (2010) and Xing et al (2017) stated, the observed Chl increase at depth is due to very high CDOM (which is a consequence of the anoxic conditions prevailing at depth in the Black Sea) and non-algal matter concentrations that can affect the chlorophyll fluorescence signal. After correcting the profile according to Xing et al (2017), Chl concentrations below 100 m are zero. The profile from the South Atlantic subtropical gyre mostly exhibits a nonzero dark offset, which is removed in quality control (Fig.…”
Section: Quality-controlled Vertical Profilesmentioning
confidence: 92%
See 3 more Smart Citations
“…As Proctor and Roesler (2010) and Xing et al (2017) stated, the observed Chl increase at depth is due to very high CDOM (which is a consequence of the anoxic conditions prevailing at depth in the Black Sea) and non-algal matter concentrations that can affect the chlorophyll fluorescence signal. After correcting the profile according to Xing et al (2017), Chl concentrations below 100 m are zero. The profile from the South Atlantic subtropical gyre mostly exhibits a nonzero dark offset, which is removed in quality control (Fig.…”
Section: Quality-controlled Vertical Profilesmentioning
confidence: 92%
“…Profile-byprofile analysis-visualization, number of invalid points, and related origin are available on http://seasiderendezvous.eu. Profiles collected in areas such as the Black Sea and subtropical regions were further corrected for the contribution of fluorescence originating from non-algal matter following procedures described in Xing et al (2017). The correction was applied when Chl and FDOM concentrations were positively correlated below the depth at which Chl was supposed to be zero (for equations and quantitative metrics see .…”
Section: Quality Control Of Vertical Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional dark count, a deep‐offset correction (Schmechtig et al 2014), generated from the mean deep fluorescence between 300 m and 400 m was subtracted from the profiles. As our seagliders did not have FDOM sensors attached during deployment, we are unable to determine the contribution of deep sea red fluorescence on our in situ dark counts (Xing et al ). Cleaning, despiking, and smoothing steps were performed on the fluorescence data.…”
Section: Methodsmentioning
confidence: 99%